The Role of Intraorganellar Ca(2+)In Late Endosome–Lysosome Heterotypic Fusion and in the Reformation of Lysosomes from Hybrid Organelles - Pryor, Paul R. (The Rockefeller University Press, 2000)
We have investigated the requirement for Ca(2+) in the fusion and content mixing of rat hepatocyte late endosomes and lysosomes in a cell-free system. Fusion to form hybrid organelles was inhibited by 1,2-bis(2-aminophenoxy) ethane-N,N,N′,N′-tetraacetic acid (BAPTA), but not by EGTA, and this inhibition was reversed by adding additional Ca(2+). Fusion was also inhibited by methyl ester of EGTA (EGTA-AM), a membrane permeable, hydrolyzable ester of EGTA, and pretreatment of organelles with EGTA-AM showed that the chelation of lumenal Ca(2+) reduced the amount of fusion. The requirement for Ca(2+) for fusion was a later event than the requirement for a rab protein since the system became resistant to inhibition by GDP dissociation inhibitor at earlier times than it became resistant to BAPTA. We have developed a cell-free assay to study the reformation of lysosomes from late endosome–lysosome hybrid organelles that were isolated from the rat liver. The recovery of electron dense lysosomes was shown to require ATP and was inhibited by bafilomycin and EGTA-AM. The data support a model in which endocytosed Ca(2+) plays a role in the fusion of late endosomes and lysosomes, the reformation of lysosomes, and the dynamic equilibrium of organelles in the late endocytic pathway.